Atomistic fingerprint of hyaluronan-CD44 binding - Vuorio, Joni; Vattulainen, Ilpo; Martinez-Seara, Hector (PLoS computational biology, 2017)
Hyaluronan is a polyanionic, megadalton-scale polysaccharide, which initiates cell signaling by interacting with several receptor proteins including CD44 involved in cell-cell interactions and cell adhesion. Previous studies of the CD44 hyaluronan binding domain have identified multiple widespread residues to be responsible for its recognition capacity. In contrast, the X-ray structural characterization of CD44 has revealed a single binding mode associated with interactions that involve just a fraction of these residues. In this study, we show through atomistic molecular dynamics simulations that hyaluronan can bind CD44 with three topographically different binding modes that in unison define an interaction fingerprint, thus providing a plausible explanation for the disagreement between the earlier studies. Our results confirm that the known crystallographic mode is the strongest of the three binding modes. The other two modes represent metastable configurations that are readily available in the initial stages of the binding, and they are also the most frequently observed modes in our unbiased simulations. We further discuss how CD44, fostered by the weaker binding modes, diffuses along HA when attached. This 1D diffusion combined with the constrained relative orientation of the diffusing proteins is likely to influence the aggregation kinetics of CD44. Importantly, CD44 aggregation has been suggested to be a possible mechanism in CD44-mediated signaling.
Keywords: Hyaluronan Receptors; Protein Binding; výpočetní biologie; vazba proteinů; Molecular Dynamics Simulation; Protein Conformation; simulace molekulární dynamiky; lidé; Hyaluronic Acid; konformace proteinů; kyselina hyaluronová; Computational Biology; Humans; antigeny CD44